Knowledge, attitude, and practice towards face mask use among residents of Greater Chennai Corporation, India, March 2021 - Nagarajan, Ramya; Rubeshkumar, Polani; Jagadeesan, Murugesan; Raju, Mohankumar; Sakthivel, Manikandanesan; Murali, Sharan; Sendhilkumar, Muthappan; Ilangovan, Kumaravel; Harikrishnan, Dineshkumar; Venkatasamy, Vettrichelvan; Ganeshkumar, Parasuraman; Kaur, Prabhdeep (Frontiers in Public Health, 2022)
Background: Wearing a mask is one of the simplest ways to reduce the spread of COVID-19. Studies reported poor mask compliance in Chennai, India. Hence, we described the knowledge, attitude, and practice regarding mask use among adults (≥18 years) in Chennai, Tamil Nadu, India. Methods: We conducted a cross-sectional survey among residents of Greater Chennai Corporation in March 2021. We estimated the sample size to be 203 per strata (slum and non-slum). We used a simple random sampling technique to select 20 locations using a digital map in the slum and non-slum areas. After reaching the location chosen, we selected 10 consecutive households and one adult (≥18 years of age) from each household. We used a validated, semi-structured questionnaire for collecting data regarding knowledge, attitudes, and practices for mask use. We estimated proportions and 95% CI for key variables and compared the variables between slums and non-slums. Results: Of 430 participants included in the study, 51.4% were males. The mean (S.D.) age of the participants was 41.1 (14.6) years. The majority (86.7%) of the participants felt that wearing a mask helped in reducing the spread of coronavirus and the knowledge differed (p-value <0.05) between the slum (81.4%) and non-slum (92.3%). Nearly half (46.5%) of the participants did not like being forced to wear the mask. About 63.9% of the participants reported the practice of mask use while going out which was similar across slums and non-slums. Conclusion: Although the knowledge regarding mask use was good among the public, the attitude was unfavorable. We suggest continuous reinforcement by spreading awareness and educating the community on the appropriate use of the mask.